Gambaran Orientasi Masa Depan pada Mahasiswa Ditinjau dari Jenis Kelamin dan Jurusan Studi di Universitas Negeri Padang - Hambali Amri; Niken Hartati (AHKAM, 2026)
Future orientation describes how individuals perceive and project themselves into the future and has become crucial in the context of rising unemployment among university graduates in Indonesia, as indicated by February 2024 data from Badan Pusat Statistik (BPS), which reported an open unemployment rate of 4.82% and an increase in unemployment among higher education graduates from 5.52% to 5.63%. This condition suggests that some students do not yet have optimal future planning. This study aimed to examine differences in future orientation between male and female students at Universitas Negeri Padang. A descriptive quantitative approach was employed, using a questionnaire developed based on Nurmi’s dimensions of future orientation. The research subjects consisted of 188 active students of Universitas Negeri Padang selected through probability sampling. Data were analyzed using descriptive statistics with the aid of SPSS 26 for Windows. The analysis showed that the significance value for future orientation by gender was 0.069 (> 0.05), by socioeconomic status was 0.942 (> 0.05), and by field of study was 0.052 (> 0.05). These findings indicate that there are no significant differences in students’ future orientation in terms of gender, socioeconomic status, or field of study. Overall, the results suggest that the influence of traditional demographic factors on students’ future orientation is diminishing in line with increasingly equitable access to education and opportunities available to students.